2007
DOI: 10.1086/519740
|View full text |Cite
|
Sign up to set email alerts
|

Differential Kinetics and Molecular Recognition Mechanisms Involved in Early Versus Late Growth PhaseStaphylococcus aureusCell Binding to Platelet Layers under Physiological Shear Conditions

Abstract: The results presented here demonstrate a differential mechanism and binding efficiency for the adhesion of early versus late growth phase S. aureus to immobilized platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…All of the early S. aureus studies were carried out under static or non-physiological stirring conditions and therefore it is difficult to relate these studies to the disease processes. Studies using a cone and plate viscometer (a device that shears cells at a given flow rate) have demonstrated that protein A, ClfA, SdrC, SdrD and SdrE are important in thrombus formation (George et al, 2007;George et al, 2006;Pawar et al, 2004). However, extremely high shear rates were used in these rheological studies.…”
Section: Platelet-bacterial Interactions: the Staphylococcusmentioning
confidence: 99%
“…All of the early S. aureus studies were carried out under static or non-physiological stirring conditions and therefore it is difficult to relate these studies to the disease processes. Studies using a cone and plate viscometer (a device that shears cells at a given flow rate) have demonstrated that protein A, ClfA, SdrC, SdrD and SdrE are important in thrombus formation (George et al, 2007;George et al, 2006;Pawar et al, 2004). However, extremely high shear rates were used in these rheological studies.…”
Section: Platelet-bacterial Interactions: the Staphylococcusmentioning
confidence: 99%
“…Studies using a cone and plate viscometer have shown that protein A, ClfA, SdrC, SdrD and SdrE are important in thrombus formation [67][68][69]. However, extremely high shear rates were used in these rheological studies.…”
Section: Staphylococcal Platelet Interactionsmentioning
confidence: 99%
“…58 Platelets therefore play an important role in the pathogenesis of endovascular infection by providing an adhesive surface for bacterial binding on blood vessel walls. 10 While a number of studies have focused on the molecular mechanisms responsible for platelet-staphylococcal binding, 18,19,45 the impact of bacterial presence on thrombus formation in whole blood is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies in our laboratory and others have demonstrated staphylococcal adhesion to collagen, 32,33,36 fibrinogen, 23,34,35 von Willebrand factor, 24,34,35 and platelets. 18,19,33 Therefore the site of a growing thrombus provides a host of surfaces for S. aureus adhesion and subsequent integration. Fluid shear is an important parameter in these interactions and has been shown to influence the specific mechanisms of binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation